Volumetric brain changes in migraineurs from the general population. (14th November 2017) - Palm-Meinders, Inge H.; Arkink, Enrico B.; Koppen, Hille; Amlal, Souad; Terwindt, Gisela M.; Launer, Lenore J.; van Buchem, Mark A.; Ferrari, Michel D.; Kruit, Mark C.
Abstract : Objective: To assess volumetric brain changes in migraineurs from the general population compared with controls. Methods: Structural brain changes in migraineurs from the general population-based MRI Cerebral Abnormalities in Migraine, an Epidemiologic Risk Analysis (CAMERA)-2 observational cohort study were assessed by state-of-the-art voxel-based morphometry. T1-weighted MRIs of 84 migraineurs (52 with aura, 32 without aura) and 35 headache-free controls were evaluated. Regional volumes were compared voxelwise, corrected for age, sex, and total intracranial volume, with region-of-interest and whole-brain analyses. Results: In region-of-interest analyses, migraineurs showed decreased gray matter volume in the visual areas V3 and V5 of the right occipital cortex compared to controls ( p < 0.05, familywise error correction). Post hoc analyses revealed that similar changes were present regardless of migraine aura status, disease activity (>1 year attack-free [inactive] vs ≥1 attack within the last year [active] and attack frequency [⩽1 (low) vs ≥1 attack per month [high]). In exploratory whole-brain analyses ( p < 0.001, uncorrected for multiple comparisons), we identified additional structural differences in migraineurs in other cortical and subcortical areas, including white matter tracts, that are particularly involved in visual processing. Conclusions: Migraineurs from the general population showed small volumetric brain changes, mainly in cortical areas involved in visual motion processing, compared to controls. The presence of morphologic changes regardless of the presence of migraine aura or disease activity suggests that migraines with and without aura share common pathophysiologic pathways and suggests that these changes are (partially) irreversible or might have been present throughout life.